The Spectral Einstein Functional for the Nonminimal de Rham-Hodge Operator (Communications in Mathematical Research, 2025)
In this paper, we give the definitions of the non-self-adjoint spectral triple and its spectral Einstein functional. We compute the spectral Einstein functional associated with the nonminimal de Rham-Hodge operator on even-dimensional compact manifolds without boundary. Finally, several examples of the non-self-adjoint spectral triple are listed.